2017
DOI: 10.1007/978-3-319-64027-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Hedonic or Social? Exploring Antecedents and Consequences of Virtual Reality Rollercoaster Usage

Abstract: During the last years, various media technologies such as Augmented Reality (AR) and Virtual Reality (VR) have gained increased attention in consumer markets and tourism. For theme parks, especially those with rollercoasters, wearable VR devices are expected to be associated with various benefits for tourists' experience. Therefore, adventure park managers with VR rollercoasters have a keen interest in understanding the drivers and psychological mechanisms of their visitors, especially those associated with ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
0
21
0
3
Order By: Relevance
“…VR can be defined as "an artificial environment that is created with software and presented to the user in such a way that the user suspends belief and accepts it as a real The Interactive Applications (IAs) in Academic Libraries: Challenges and Opportunities DOI: http://dx.doi.org/10.5772/intechopen.95767 environment" [14]. Furthermore, it is the computer-generated simulation of a three-dimensional image or environment that can be interacted with in a seemingly real or physical way by a person using special electronic equipment, such as a helmet with a screen inside or gloves fitted with sensors (see Figure 3) [15].…”
Section: Virtual Reality (Vr)mentioning
confidence: 99%
See 2 more Smart Citations
“…VR can be defined as "an artificial environment that is created with software and presented to the user in such a way that the user suspends belief and accepts it as a real The Interactive Applications (IAs) in Academic Libraries: Challenges and Opportunities DOI: http://dx.doi.org/10.5772/intechopen.95767 environment" [14]. Furthermore, it is the computer-generated simulation of a three-dimensional image or environment that can be interacted with in a seemingly real or physical way by a person using special electronic equipment, such as a helmet with a screen inside or gloves fitted with sensors (see Figure 3) [15].…”
Section: Virtual Reality (Vr)mentioning
confidence: 99%
“…MR is defined as "the merging of real and virtual worlds to produce new environments and visualizations where physical and digital objects co-exist and interact in real-time" [16]. Figure 4 indicates Mixed reality takes place not only in the physical world or the virtual world but is a mix of reality and virtual reality [15]. Simply, Mixed reality is a hybrid of VR and AR and aims to offer the best of both worlds.…”
Section: Mixed Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important as existing studies only look at the potential of using VR to enhance hospitality and tourism experiences with only few case studies actually implementing it in the long run. One of few examples as part of the visitor economy must be theme parks, which were one of the early adopters of VR to gamify attractions such as rollercoasters (Jung et al, 2018).…”
Section: Vr In Hospitality and Tourismmentioning
confidence: 99%
“…Late studies have repeatedly suggested that VR has the potential to enhance the consumer experience by generating an immersive environment aiming to engage customers with brands and products (Huang et al, 2016). While VR research in the hospitality and tourism industry has been increasing (Griffin et al, 2017;Han et al, 2017;Jung et al, 2018;, the majority of studies focus on the potential virtual enhancement and influence on the visitor experience in line with specific products and contexts such as museums, virtual showrooms or VR enhanced roller coasters in theme parks. We are now at a stage where we comprehend the current technological capabilities of VR as well as have touched upon a number of potential benefits VR could provide for our industry.…”
Section: Introductionmentioning
confidence: 99%